2017
DOI: 10.1161/atvbaha.117.309089
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Fstl1 (Follistatin-Like 1) From the Endocardial/Endothelial Lineage Causes Mitral Valve Disease

Abstract: We report on a mouse model in which deletion of Fstl1 from the endocardial/endothelial lineage results in deformed mitral valves, which cause regurgitation, heart failure, and early cardiac death. The findings provide a potential molecular target for the clinical research into myxomatous mitral valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 63 publications
1
38
0
Order By: Relevance
“…Fstl1 is a TGF‐β superfamily binding protein and has been identified as a bone morphogenetic protein 4 (BMP4) antagonist controlling embryonic development . Fstl1 is also involved in many pathological processes, including carcinogenesis and metastasis, inflammatory and autoimmune diseases, cardiovascular diseases, and organ fibrosis . Despite extensive studies for Fstl1 have been performed, no structural information is available for this important molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fstl1 is a TGF‐β superfamily binding protein and has been identified as a bone morphogenetic protein 4 (BMP4) antagonist controlling embryonic development . Fstl1 is also involved in many pathological processes, including carcinogenesis and metastasis, inflammatory and autoimmune diseases, cardiovascular diseases, and organ fibrosis . Despite extensive studies for Fstl1 have been performed, no structural information is available for this important molecule.…”
Section: Discussionmentioning
confidence: 99%
“…1 Fstl1 is also involved in many pathological processes, including carcinogenesis and metastasis, inflammatory and autoimmune diseases, cardiovascular diseases, and organ fibrosis. 16,[31][32][33][34] Despite extensive studies for Fstl1 have been performed, no structural information is available for this important molecule. In our report, we solved the high-resolution crystal structure of FK domain of Fstl1, analyzed its unique characteristics, Immunoblotting was performed to detect the protein levels of α-SMA and β-actin (n = 4 per group), three repetitive experiments were shown for each group and investigated its contribution to the function of full-length Fstl1.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently prepared a global and conditional knockout of Follistatin‐like 1 ( Fstl1 ) (Prakash et al, ; Sylva et al, ) which both show congenital abnormalities (see below). FSTL1 is a secreted glycoprotein (OMIM 605547), belonging to SPARC family of proteins (Sylva, Moorman, & Hoff, ), and is a potential prognostic marker for cardiovascular disease (Widera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyocyte‐specific deletion of Fstl1 using αMHC‐Cre (Shimano et al, ) or fibroblasts specific deletion using S100A4‐Cre (Tanaka et al, ) resulted in viable offspring with no reported developmental defects. However, conditional ablation of Fstl1 from the endocardial/endothelial lineage using Tie2‐Cre ( Fstl1 endoKO) results in neonatal lethality between 2 and 4 weeks after birth (Prakash et al, ). These Fstl1 endoKO mice showed profound cardiac and valve defects, including an enlarged stressed heart and long and thick atrioventricular valves, displaying a myxomatous phenotype and being dysfunctional (Prakash et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation